Potential skin problems of diabetes mellitus patients: a review - H. Bing Thio; Hardyanto Soebono; Iryani Andamari (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
Diabetes mellitus (DM) is one of the common metabolic disorders, and a major part of chronic diseases, the prevalence of which tends to increase due to multifactor. Blood vessels, kidneys, lungs, and skin are among the organs that are affected. The first problem that arises, or commonly exists among one-third of diabetics, are problems with their skin, although skin lesions may develop along with the progress of the disease, or can occur during the later phase of DM. The prevalence and symptoms of skin problems in type 1 DM (T1DM) and type 2 DM (T2DM) are often unclear, and at the beginning of the course of the diseases they often go undiagnosed. Several theories regarding the pathophysiology of DM can be used as a logical reference for the early identification and diagnosis of skin problems, aimed at preventing the worsened condition. The use of skin autofluorescence (SAF) and AGEs reader in several cases of skin problems, can also be an important marker as an adjunct to predict the possibility and progressiveness of DM. Skin problems linked to patients with DM can be categorized as strongly related to diabetes, non-specific and related to DM, skin infection in DM, and skin problems due to diabetic medication. With the current COVID-19 pandemic, there are additional demands for more critical investigation of skin problems in patients with DM. The skin problems that occur in DM may need to be examined from the early stage and it is necessary to inhibit the progression of skin problems, as well as to consider the need for multidisciplinary DM therapy.